2012
DOI: 10.2478/v10216-011-0024-9
|View full text |Cite
|
Sign up to set email alerts
|

Phytoextraction of Nickel by Selected Ornamental Plants

Abstract: Abstract:In the pot experiment the effect of increasing doses of Ni (the control, 25, 50, 75, 150, 300 mg · dm -3 substrate) on the content of this metal in individual organs of aboveground parts was investigated in three selected species of ornamental plants: Aztec marigold (Tagetes erecta L.), sunflower (Helianthus annus L.) and love-lies-bleeding (Amaranthus caudatus L.). A significant effect of increasing Ni doses on the content of this metal was found in individual organs of selected species. In Tage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It was also suggested that cultivars having low shoot/root Ni ratio had better ability to retain Ni in the roots, possibly by binding and sequestering it in the vacuoles [36], which might have contributed to the tolerance to Ni. Interspecies differences in accumulation and translocation of Ni were confirmed by Bosiacki and Wojciechowska [37] in their experiments with ornamental plant species Tagetes erecta L., Helianthus annus L. and Amaranthus caudatus L. Translocation factors (TF) as well as the portion from the total accumulated metal amount by the plant occurring in the shoots are summarized in Table 3. The TF factors correspond to the ratio of accumulated Ni amount in shoots and roots.…”
Section: Resultsmentioning
confidence: 69%
“…It was also suggested that cultivars having low shoot/root Ni ratio had better ability to retain Ni in the roots, possibly by binding and sequestering it in the vacuoles [36], which might have contributed to the tolerance to Ni. Interspecies differences in accumulation and translocation of Ni were confirmed by Bosiacki and Wojciechowska [37] in their experiments with ornamental plant species Tagetes erecta L., Helianthus annus L. and Amaranthus caudatus L. Translocation factors (TF) as well as the portion from the total accumulated metal amount by the plant occurring in the shoots are summarized in Table 3. The TF factors correspond to the ratio of accumulated Ni amount in shoots and roots.…”
Section: Resultsmentioning
confidence: 69%
“…Generally, the total amounts of chromium and nickel absorbed by the plant remained in the roots despite the fact that there were six different irrigation lines with different concentrations of Cr (VI) and Ni (II). In similar studies to ours, the higher absorbance of Ni was recorded in stems [21], whereas Ni in the leaves of sunflower have been observed to be selectively distributed to key points of the sheet (mesophyll) of the plant [17]. …”
Section: Discussionmentioning
confidence: 52%
“…The metal concentration index was caluclated from the formula C = a : b a -content in a plant growing in a polluted substrate b -content in a plant growing in an unpolluted substrate (Bosiacki and Wojciechowska 2012). Nickel concentration index in the above-ground parts of Miscanthus × giganteus of over 100 was recorded both in the fi rst and second year of plant growth in mineral soil and in a mixture of soil with peat which was contaminated with nickel at 600 mg dm -3 (Table 5).…”
Section: Resultsmentioning
confidence: 99%